User's Manual for GeogridBridge 3.0 - A Guide to the Load Displacement Compatibility Method (LDC) for Design of Column-Supported Embankments - Sloan Joel A; Hummel Elise; McGuire Michael; Hunstein Eric (American Society of Civil Engineers (ASCE), 2024)
Sponsored by the Geosynthetics Technical Committee of the Technical Coordination Council of the Geo-Institute of ASCEThis details how to use the GeogridBridge 3.0 (GGB3) spreadsheet, which utilizes the Load Displacement Compatibility (LDC) method for the design of column-supported embankments (CSEs) and walks through two worked examples to illustrate the use of the spreadsheet. This book supplements Theory Manual for the Load Displacement Compatibility Method (LDC) for Design of Column-Supported Embankments, GSP 356, and other geotechnical resources and tools, listed within this manual, to assist engineers with the design and construction of column-supported embankments.This manual intends to be an informed, continuously updated guide for geotechnical engineers and engineering professionals looking to incorporate the GGB3 spreadsheet into standard engineering practices regarding the design of column-supported embankments.